Simulation Study on the Investment Casting Process of a Low-Cost Titanium Alloy Gearbox based on ProCAST - Qiang Liao; Peng Ge; Guangxuan Lu; Yang Song; Wenhui Ye; Jianping Gao; Xian Luo (Advances in Materials Science and Engineering, 2022)
A model of investment casting of a titanium alloy gearbox based on the ProCAST software was established in this work, and the simulated result was used to optimize the casting process. The flow and temperature field of casting were simulated based on an actual pouring process. Casting defects and the solidification process were analyzed. The results show that the defects can be predicted by the simulation result exactly, and the simulated temperature field is in accordance with the actual process. Shrinkage and porosity are observably alleviated by remodelling the casting mould. The casting temperature field and solidification simulation results show that the casting defects arise from hot spots and heat accumulation. The temperature-time curve of different representative location nodes of casting further confirms the defect simulation results. In addition, the use of low-cost alloy elements reduces raw material costs. Compared with TC4 alloy, the mechanical properties of the casting remain unchanged.